(untitled) (Research, Society and Development, 2021)
Introduction: The correct management of Health Services Waste (RSS) has been one of the biggest challenges of health establishments, since they are heterogeneous in nature and need to be labeled in order to be segregated correctly. Pharmacists must also be concerned with the waste generated by activities in their workplaces, demanding from other employees a conscious position and willingness to cooperate in the search for solutions. Methodology: The literature search was carried out in SciELO (Scientific Electronic Lirary Online), Academic Google and Lilacs - Bireme (Latin American and Caribbean Literature in Health Sciences) databases. The following inclusion criteria were established: articles available in full, in Portuguese and English, from 2014 to 2021 with free access related to the subject. Finally, 10 studies were used to integrate this review article. Results and discussion: Based on these studies, we realize the real need for pharmaceutical care in the planning and handling program for solid waste in healthcare facilities. Conclusion: The pharmacist is essential in the care, planning and handling program of solid waste because he is eager to take risks that the population runs if it is wrongly disposed of, which can put countless lives at risk. What is expected is that more and more such professionals engage in this management so that the health team has excellent care within their establishments.